Susceptibility to vaccine-preventable diseases and vaccination adherence among healthcare workers in Italy: A cross-sectional survey at a regional acute-care university hospital and a systematic review. Issue 2 (1st February 2017) - Leone Roberti Maggiore, Umberto; Scala, Carolina; Toletone, Alessandra; Debarbieri, Nicoletta; Perria, Mauro; D'Amico, Beatrice; Montecucco, Alfredo; Martini, Mariano; Dini, Guglielmo; Durando, Paolo
ABSTRACT: Healthcare Workers (HCWs) have an increased risk both to acquire and to spread vaccine preventable diseases (VPDs) both to their colleagues and, especially, to vulnerable patients. The prevention of occupational hazards among HCWs is based on proper adoption of the standard and additional precautions, immunizations, and secondary preventive measures, such as post-exposure prophylaxis. Moreover, HCWs are often referred to as the most trusted source of vaccine-related information for their patients. In the present article, we report the findings of a cross-sectional study investigating the compliance to vaccinations among HCWs employed at the Obstetric Unit of a regional acute-care University Hospital in Northern Italy. Furthermore, a systematic review of the literature for some VPDs (i.e., HBV, measles, rubella, varicella and influenza) was performed, over a 17-year period, in order to update the socio-demographic and professional characteristics, the susceptibility status and the vaccination rates among HCWs in Italy.